The Influence Of Brewing Techniques (Syphon, French Press, Moka Pot) On The Sensory Attributes Of Robusta And Arabic Coffe - Nur Paidah (JURAGAN - Jurnal Agroteknologi, 2025)
According to the International Coffee Organization, in 2016 Indonesia became the fourth largest coffee producing country in the world. The commonly known types of coffee are Arabica and Robusta. The taste of coffee is influenced by several factors such as the quality of the soil where the coffee is grown, the maturity of the coffee beans when harvested, the location of the coffee plantation, coffee production, coffee processing, roasting and brewing. The diversity of various types of coffee beans will become more visible and visible if they are brewed using various brewing methods. Currently, many kinds of tools have been created in the development of serving and brewing Manual Brewing, these tools include, namely V60, Aeropress, French Press, Moka pot, Siphon, Chemex, Cezve, and others. This article tries to summarize several brewing techniques that exist around the community to determine the quality of the coffee brew produced using this equipment. Robusta coffee is more suitable for brewing using the siphon brewing technique because the aroma and color produced from this brewing are better than using other brewing techniques.